2004
DOI: 10.1002/adma.200306340
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Modified Calcium Phosphates as Novel Materials for Bisphosphonate Delivery

Abstract: though the reactable surface area of this Pt is large. This is probably because the methanol molecules have difficulty reaching the surfaces of the Pt particles inside the SWNHs; when Pt particles are deposited outside the SWNHs there is no obstacle to methanol decomposition on the Pt surfaces.In summary, we have found that Pt particles are preferentially deposited inside the nanospaces of SWNHs and located near the defects. Furthermore, they have an upper limit in their sizes and quantities. We have therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 28 publications
3
42
1
Order By: Relevance
“…The surface state of the HA has been checked by SEM, but no change due to Zoledronate grafting was observed (data not shown). The zoledronate was grafted by ion exchange with the phosphate ions from the HA [20]. Based on this data, the HA coating does not become saturated with bisphosphonate, but an equilibrium is created between the phosphate groups and the bisphosphonate groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface state of the HA has been checked by SEM, but no change due to Zoledronate grafting was observed (data not shown). The zoledronate was grafted by ion exchange with the phosphate ions from the HA [20]. Based on this data, the HA coating does not become saturated with bisphosphonate, but an equilibrium is created between the phosphate groups and the bisphosphonate groups.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, 19 implants were immersed for 48 h in 5 ml of aqueous zoledronate solutions of variable concentration: 2.25 10 À6 , 2.25 10 À5 , 2.25 10 À4 , and 2.25 10 À3 mol l À1 , leading to modified coatings. Then, the remaining amount of zoledronate in the supernatant at the end of the reaction was determined as previously described [20], using a protocol based on the Ames method [2] for the determination of the phosphorus content in solution. By difference with the initial amount of zoledronate present in solution, the zoledronate loading onto the implants was deduced, namely, 1.9-2.4 Ag zoledronate per implant (corresponding to a full incorporation of zoledronate), 8-9 Ag zoledronate per implant (corresponding to a 35% incorporation ratio), and 16 Ag zoledronate per implant (corresponding to a 7% incorporation ratio).…”
Section: Grafting Of Zoledronatementioning
confidence: 99%
“…Two samples were used as controls, while the remaining 4 samples were soaked for 48h in 5ml ultrapure water solutions of 2.25 10 -5 mol L -1 of Zoledronate (1-hydroxy-2-[(1H-imidazole-1-yl)ethylidene] 1-bisphosphonic acid disodium salt) supplied by Novartis Pharmaceuticals AG, Basel, Switzerland. The amount of zoledronate loaded onto the implants was calculated to be 2.1 μg for each implant (Josse et al, 2004).…”
Section: Implantsmentioning
confidence: 99%
“…It has been shown recently that a biphosphonate incorporated on to titanium implants increased bone density locally in the peri-implant region. 101 The effect of the antiresorptive drug seems to be limited to the vicinity of the implant. Experimental in vivo studies have demonstrated the absence of negative effects but only a slight increase in dental implant osseointegration.…”
Section: Incorporation Of Biologically Active Drugs Into Titanium Denmentioning
confidence: 99%
“…Experimental in vivo studies have demonstrated the absence of negative effects but only a slight increase in dental implant osseointegration. 101,102 Other experimental studies using plasma-sprayed HA-coated dental implants immersed in pamidronate or zoledronate demonstrated a significant increase in bone contact area. 104,106 The main problem lies in the grafting and sustained release of antiresorptive drugs on the titanium implant surface.…”
Section: Incorporation Of Biologically Active Drugs Into Titanium Denmentioning
confidence: 99%